Literary Representations Of Post-Colonial Struggles: A Study Of Indonesian and Kazakh Literature - Eka Rina Febriyani; Muhammad Zanuar Habib; Iswatul Eva Mudhalifah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This paper investigates how post-colonial themes of identity, resistance, and cultural survival are represented in Indonesian and Kazakh literature. By examining key literary works, the study explores the authors’ portrayal of the impacts of colonialism and the subsequent struggles for cultural autonomy. Drawing on post-colonial theory, this paper analyzes how both Indonesian and Kazakh writers use narrative strategies to reclaim history, voice, and cultural heritage.